TAṬFĪF DAN MISLABELLING DALAM PERDAGANGAN MODERN: ANALISIS MAʿNĀ-CUM-MAGHZĀ QS. AL-MUṬAFFIFĪN [83]:1–6 - Hasdin Has, Muhammad; Aminudin, Aminudin; Saputra, Faisal Saleh Julian (IAIN KENDARI, 2026)
Mislabelling is a form of food fraud that has become increasingly prevalent in modern trade systems and has the potential to harm consumers through the manipulation of product information. This study aims to examine the relevance of the concept of taṭfīf in Q.S. al-Muṭaffifīn [83]:1–6 to the phenomenon of mislabelling using the Maʿnā-cum-Maghzā hermeneutical approach. This research employs a qualitative library research method with a descriptive-analytical framework. Primary sources consist of Q.S. al-Muṭaffifīn [83]:1–6 and classical to contemporary Qur’anic commentaries, while secondary sources include literature on food fraud, Islamic business ethics, and Information Asymmetry theory. The findings reveal that taṭfīf is not limited to the physical reduction of weights and measures but also encompasses the deprivation of rights through information manipulation. Mislabelling shares a substantive similarity with taṭfīf as both exploit information asymmetry for unilateral gain. This study argues that information transparency represents a contemporary manifestation of the Qur’anic principle of justice embodied in Q.S. al-Muṭaffifīn and serves as an ethical foundation for consumer protection and market integrity.